Cyprus : First Post-Program Monitoring Discussions-Press Release; Staff Report; and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses the First Post-Program Monitoring Discussions with Cyprus. Cyprus's economic recovery has continued to strengthen in the 15 months since it exited from the IMF-supported program. Economic growth has been broad based and reached a robust 2.8 percent in 2016, supporting a sharp drop in the unemployment rate. Excluding large one-off imports, the current account deficit continued to narrow and earlier gains in price competitiveness have been preserved. The fiscal primary surplus reached a sizable 2.3 percent of GDP in 2016, supported by reforms undertaken in previous years and improving cyclical conditions. Over the medium term, the pace of growth is expected to gradually ease to just over 2 percent.